Răspunsuri

2014-11-05T15:34:19+02:00
A+B=1010⇒A=1010-B  acum inlocuim.  A-B=956⇒1010-B-B=956⇒1010-2B=956   2B=1010-956⇒2B=54⇒B=27                                                                              A-B=956⇒A-27=956⇒A=956+27⇒A=983                                                           C=983·42⇒C=41286                                                                                           V: 983+27=1010 (A+B)     983-27=956 (A-B)
Merci!
cu placere dar evoluiaza si tu te rog ca cel mai bun ,ca sa primesc 3 puncte